Online Learning during the Pandemic in Indonesia: A Case Study on Digital Divide and Sociality among Students - Sita Hidayah (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2022)
This paper discusses the social world of online education in Indonesia. Drawing on a qualitative study held in July to September 2021, this paper describes how students used digital technologies for both education and social connection purposes during the COVID-19 restriction policy. In contrast to the widely assumed uniformity of online education and ubiquity of information technologies, this study identifies various digital divides ranging from unequal access to and control over digital devices and the internet to the varying degrees of students’ technological skills and participation. Sociality is used as a conceptual framework to understand students’ social interactions and networks. Data was collected from online interviews and partial participant observations with high school and university students from Jakarta, Denpasar (Bali), Magelang (Central Java), Pekanbaru (Riau), and Yogyakarta. The study concludes that the digital divide in online education exacerbates existing social inequalities. Simultaneously, online education enables the construction of new forms of stratification and relationships